(untitled) (Journal of Educational Sciences, 2017)
In the article the problem of teaching methods in selected courses of plasma physics. The content and value of an understanding of plasma in General. Talks about the problems of the teaching of these courses through online learning. Describes the application of an electric gas discharge for plasma in the laboratory and in applied technical methods is also shown that the gas discharge is the basic method of plasma production in the laboratory. Moreover, examples of application of specific methods and their analysis. Made a comprehensive analysis on interactive methods and investigated their application results. In teaching the courses «Selected issues of plasma physics» focuses on the impact of the development of creative abilities of students in the new lesson. On the basis of educational and methodical complex of the course made the above electronic textbook on the modern system of education.